Characterization of implicit and explicit mind-reading in children with autism based on eye movements - Lu, Haidan; Niu, Juanli; Wang, Jiaxin; Liu, Min; Xu, Mingyu (Frontiers in Psychiatry, 2024)
Objective: This study aimed to investigate differences in mind-reading abilities between children with autism and typically developing children across various tasks. Methods: Sixteen children with autism (aged 5-8 years) were compared to 16 typically developing children matched in language ability. The unexpected location task and unexpected content task were used to assess implicit and explicit mind-reading abilities using an eye tracker and illustrated storybooks. Results:For implicit mind,using differential looking socres shows a no significant difference between the scores of children with autism and typically developing children in the implicit tasks (P=0.399).However,the pupil size show some significant difference between two groups.Second, for the explicit,a significant difference between the scores of children with autism and typically developing children in the explicit tasks (P=0.006). Additionally, only a significant correlation between implicit and explicit mind-reading abilities in children with autism in the unexpected location task was found. Conclusion:The mechanism of implicit mind-reading still not very clear. Pupil-Linked arousal response can be consider as a further tool. Further research on implicit and explicit mind-reading abilities is warranted.